Saccadic entropy of head impulses in acute unilateral vestibular loss - Li-Chun Hsieh (Journal of the Formosan Medical Association, 2017)
To evaluate the complexity of vestibular–ocular reflex (VOR) in patients with acute unilateral vestibular loss (AUVL) via entropy analysis of head impulses. Methods: Horizontal head impulse test (HIT) with high-velocity alternating directions was used to evaluate 12 participants with AUVL and 16 healthy volunteers. Wireless electro-oculography and electronic gyrometry were used to acquire eye positional signals and head velocity signals. The eye velocity signals were then obtained through differentiation, band-pass filtering. The approximate entropy of eye velocity to head velocity (RApEn) was used to evaluate chaos property. VOR gain, gain asymmetry ratio, and RApEn asymmetry ratio were also used to compare the groups. Results: For the lesion-side HIT of the patient group, the mean VOR gain was significantly lower and the mean RApEn was significantly greater compared with both nonlesion-side HIT and healthy controls (p < 0.01, one-way analysis of variance). Both the RApEn asymmetry ratio and gain asymmetry ratio of the AUVL group were significantly greater compared with those of the control group (p < 0.05, independent sample t test). Conclusion: Entropy and gain analysis of HIT using wireless electro-oculography system could be used to detect the VOR dysfunctions of AUVL and may become effective methods for evaluating vestibular disorders.